2012
DOI: 10.1890/1051-0761-22.5.1547
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of avian and small-mammal response to fire severity and fire surrogate treatments in U.S. fire-prone forests

Abstract: Abstract. Management in fire-prone ecosystems relies widely upon application of prescribed fire and/or fire surrogate (e.g., forest thinning) treatments to maintain biodiversity and ecosystem function. Recently, published literature examining wildlife response to fire and fire management has increased rapidly. However, none of this literature has been synthesized quantitatively, precluding assessment of consistent patterns of wildlife response among treatment types. Using meta-analysis, we examined the scienti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
108
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(123 citation statements)
references
References 54 publications
(80 reference statements)
13
108
2
Order By: Relevance
“…patches of unburned vegetation, snags, downed wood), burned habitats cannot be considered entirely equivalent to early seral states. Much attention has been focused on how communities of organisms change from before to immediately after fires [24,25], or whether communities show resilience to fire over multi-decadal time frames (e.g. 20-100 years) [10,26,27], with little focus on how communities change during the potentially transformative early years following fire.…”
Section: Introductionmentioning
confidence: 99%
“…patches of unburned vegetation, snags, downed wood), burned habitats cannot be considered entirely equivalent to early seral states. Much attention has been focused on how communities of organisms change from before to immediately after fires [24,25], or whether communities show resilience to fire over multi-decadal time frames (e.g. 20-100 years) [10,26,27], with little focus on how communities change during the potentially transformative early years following fire.…”
Section: Introductionmentioning
confidence: 99%
“…Grouping species into relevant niches or categories is not always an easy task (Fontaine and Kennedy 2012). Hence, this approach demands good knowledge of the species' ecologies.…”
Section: Ecological Grouping and Functional Diversity Measuresmentioning
confidence: 99%
“…A meta-analysis of avian and small-mammal responses to wildfire, thinning, and thinning plus prescribed fire showed that most short-term responses at fine spatial scales mimicked species responses to low-and moderateseverity wildfire (Fontaine and Kennedy 2012). The majority of the responses to the fuel treatments were neutral; thinning combined with prescribed fire had the most positive species responses; and species responded to high-severity wildfire with the strongest reaction (both positive and negative) (Fontaine and Kennedy 2012).…”
Section: Effects On Wildlifementioning
confidence: 99%
“…Several wildlife species in the Sierra Nevada utilize the forest structure and early-successional conditions that occur following a high-severity fire, which are not well approximated by prescribed fire or thinning treatments (Fontaine and Kennedy 2012;Hutto 2008;. The black-backed woodpecker, a post-fire specialist that searches for insects in dead trees, may benefit from firescorched dead trees following prescribed fires with high intensities, or from leaving clumps of dense trees during thinning operations that can subsequently burn at higher severities (Hutto 2008).…”
Section: Effects On Wildlifementioning
confidence: 99%
See 1 more Smart Citation